Evaluation of the relationship between eating behaviour and body mass index in adults: Eating Behaviour and Body Mass Index - Erenoglu Son, Nazan (Progress in Nutrition, 2023)
Background and aim: This study was planned to determine the eating behaviours of adults and to examine the relationship between eating behaviour and body mass index (BMI). This was a single-centre cross-sectional study. The study was conducted in ahealth institution in Afyonkarahisar, Turkey, between September 15 and November 1, 2021.Methods: The study was conducted with a total of 1,601 participants.  In the study, height, body weight, place of residence, marital status, profession, educational status of the participants, and whether they used social media were questioned and their BMI values were calculated. Also, the Three-Factor Eating Questionnaire (TFEQ-R18) was used in the study.Results: Single individuals have been determined to eat more uncontrollably, experience emotional hunger and are more sensitive to hunger than married ones. Furthermore, as the level of education decreases, uncontrolled nutrition, emotional hunger and sensitivity to hunger increase. Non-working individuals were found to experience more emotional hunger. Those living in the city centre were found to eat more uncontrollably. Obese individuals were found to eat more uncontrollably and experience emotional hunger, and moreover, not able to practice cognitive restraint.Conclusion: As per our results, some measures should be taken to protect the health of individuals and to make this sustainable by having normal body weights. Eating behaviour change is one of the first of these measures and it should start in the family at an early age.